Outcomes of robot-assisted versus conventional laparoscopic low anterior resection in patients with rectal cancer: propensity-matched analysis of the National Clinical Database in Japan. Issue 5 (23rd September 2021) - Matsuyama, T; Endo, H; Yamamoto, H; Takemasa, I; Uehara, K; Hanai, T; Miyata, H; Kimura, T; Hasegawa, H; Kakeji, Y; Inomata, M; Kitagawa, Y; et al.
Abstract: Background: Robot-assisted laparoscopic surgery has several advantages over conventional laparoscopy. However, population-based comparative studies for low anterior resection are limited. This article aimed to compare peri-operative results of robot-assisted low anterior resection (RALAR) and laparoscopy Methods: This retrospective cohort study used data from patients treated with RALAR or conventional laparoscopic low anterior resection (CLLAR) between October 2018 and December 2019, as recorded in the Japanese National Clinical Database, a data set registering clinical information, perioperative outcomes, and mortality. Of note, the registry does not include information on the tumour location (centimetres from the anal verge) and diverting stoma creation. Perioperative outcomes, including rate of conversion to open surgery, were compared between RALAR and CLLAR groups. Confounding factors were adjusted for using propensity score matching. Results: Of 21 415 patients treated during the study interval, 20 220 were reviewed. Two homogeneous groups of 2843 patients were created by propensity score matching. The conversion rate to open surgery was significantly lower in the RALAR group than in the CLLAR group (0.7 versus 2.0 per cent; P < 0.001). The RALAR group had a longer operating time (median: 352 versus 283 min; P < 0.001), less intraoperative blood loss (15 versus 20 ml; P < 0.001), a lower in-hospital mortality rate (0.1 versus 0.5 per cent; P = 0.007), and a shorter postoperative hospital stay (median: 13 versus 14 days; P < 0.001) compared with the CLLAR group. The CLLAR group had a lower rate of readmission within 30 days (2.4 versus 3.3 per cent; P = 0.045). Conclusion: These data highlight the reduced conversion rate, in-hospital mortality rate, intraoperative blood loss, and length of postoperative hospital stay for rectal cancer surgery in patients treated using robot-assisted laparoscopic surgery compared with laparoscopic low anterior resection. Abstract : A retrospective cohort study was undertaken using data from 20 220 patients who underwent robot-assisted low anterior resection (RALAR) or conventional laparoscopic low anterior resection as recorded in the National Clinical Database in Japan. The data highlight the potential benefit of RALAR in improving the conversion rate to open surgery, in-hospital mortality rate, intraoperative blood loss, and length of postoperative hospital stay for rectal cancer surgery.